A CASE STUDY OF EFL BLENDED LEARNING BASED ON SUPERSTAR LEARNING SYSTEM IN CHINA - Wan, Mei (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
The main goal of this study is to propose and develop a pedagogical approach to blended learning in an undergraduate course and evaluate the implementation process and the satisfaction of the students. With the help of the research instrument like class observation and questionnaire, a case study method is adopted in this research in order to find answers to the following questions: how should teachers do with online course design in a blended learning environment? How should teachers carry out teaching practice in a face-to-face class? Can EFL learners improve their learning competency through Superstar Learning System -based blended learning? First, the researcher reviews the literature related to the current situation of college English teaching and learning in China, the concept of blended learning, and an overview of the Superstar Learning System. Next, outlining the online course design for the book the researcher is using in her class and practising one of the texts are described. The design is then evaluated using a questionnaire given to 179 participants. Survey results show that blended learning based on Superstar Learning System can provide a flexible and dynamic learning environment and improve students’ learning competency. Contents of online courses must be designed according to students’ needs and must be developed for all components of blended learning. The results also show students’ overall satisfaction is high.